Incidence of bronchiectasis in patients with acromegaly: a cohort study - Gil, Hyun-Il; Han, Kyungdo; Hong, Sangmo; Park, Cheol-Young (Frontiers in Endocrinology, 2024)
Objective: Associations between acromegaly and several respiratory diseases, such as obstructive lung disease or sleep apnea, have been suggested, but the relationship between bronchiectasis and acromegaly is unclear. We investigated whether acromegaly is related to the development of bronchiectasis.Using the Korean National Health Insurance System database between 2006 and 2016, we studied the relationship between acromegaly and bronchiectasis in patients with acromegaly (n=2593) and controls (1:5 age-and sex-matched subjects without acromegaly, n=12965) with a mean follow-up period of 8.9 years. Cox proportional hazards regression analysis was used to assess the risk of bronchiectasis in patients with acromegaly compared with controls after adjusting for age, sex, household income, place, type 2 diabetes, hypertension, and dyslipidemia.The mean age of the participants was 47.65 years, and male subjects comprised 45.62% of the cohort. The incidence rate of bronchiectasis in patients with acromegaly was 3.64 per 1,000 person-years and was significantly higher than that in controls (2.47 per 1,000 personyears) (log-rank test p = 0.002). In multivariable Cox proportional hazards regression modeling, the risk of bronchiectasis was significantly higher in patients with acromegaly than that in controls (HR: 1.49; 95% CI: 1.15-1.94, p = 0.0025) after adjusting for age, sex, household income, place, type 2 diabetes, hypertension, and dyslipidemia.Our results suggest that acromegaly may be associated with bronchiectasis.